A Review of Sapodilla Beneficial Use, Production Status, and Propagation Technique - Budiarto, Rahmat; Dwinanda, Syahvan Rifqi; Pakpahan, Hansel Arie; Komala, Mega; Yusti, Yusti (Kultivasi, 2023)
Manilkara zapota, commonly known as sapodilla, is one of tropical fruits, originating from Central and South America that is still less popular in Indonesia, as compared to banana, citrus, mango, etc. To gain its popularity, it is crucial to review beneficial uses, existing production status and propagation techniques of sapodilla. In general, sapodilla is used for either table fresh fruit. Additionally, it contains various bioactivities in its fruit, stem, and leaves, such as antioxidant, antimicrobe, and antitumor activity; thus, become very potential for pharmaceutical purposes. The existing production data of sapodilla determine the West Java Province as the biggest production area in Indonesia, with total contribution of about 21% or 38.250 tons. In more detail, the top production area at the village level with a local sapodilla cultivar, namely Sukatali sapodilla, is found in Sukatali Village in Situraja Subdistrict, Sumedang District, West Java Province. Sapodilla can be propagated by using both reproductive and vegetative methods. Vegetative propagation of grafting is commonly used to produce shorter juvenile and uniform seedlings. However, it is highly dependent upon the grafting type, grafting season, and scion diameter. The modified cleft grafting is the best grafting type rather than cleft and veneer grafting. Several rootstocks that are commonly used for sapodilla seedling are Chrysophyllum lanceolatum and Manilkara hexandra. June-July is the best period to having grafting. The scion with a diameter of 5.02 mm is recommended due to adequate food reserves for recovery growth.